Psychological and physical condition of Japan maritime self-defense force personnel who performed disaster-relief missions after the 2011 great east Japan earthquake. (November 2020) - Takeshita, Shogo; Toda, Hiroyuki; Tanaka, Teppei; Koga, Minori; Yoshino, Aihide; Sawamura, Takehito
Abstract: The Great East Japan Earthquake, which occurred on March 11, 2011, was the most powerful earthquake ever recorded in Japan. In the present study, we examine personnel from the Japan Maritime Self-Defense Force who performed disaster relief in the earthquake's aftermath, focusing on the associated psychological and physical impacts. Overall, 8733 personnel were examined. In both July–August 2011 (M1) and July 2012 (M2), these personnel answered the Impact of Events Scale-Revised, the Kessler Psychological Distress Scale, and the Disaster Relief Questionnaire. We also analyzed the sample's physical examination records for the periods before and after the earthquake, using as controls a sample of peers who were not dispatched to the disaster area ( N  = 32, 270). The psychological examinations showed that, in M1, holding the rank of private/sergeant (odds ratio [ OR ] = 2.13), performing body-recovery duties ( OR  = 1.94), and having disaster-affected family members ( OR  = 2.13) were significant risk factors for high post-traumatic stress response (PTSR). In M2, performing body-recovery duties ( OR  = 1.45) and having disaster-affected family members ( OR  = 2.60) were significant risk factors for high PTSR. Also, being woman ( OR  = 2.18) and having disaster-affected family members ( OR  = 1.68) were significant risk factors for high general psychological distress. For the physical examinations, the mean alanine transaminase in the dispatched group (31.73 ± 25.21) was significantly higher than that in the non-dispatched group (29.56 ± 21.03). These findings suggest that personnel involved in disaster relief experience psychological impacts in the subacute stage, but that these impacts attenuate one year after the event. Highlights: Disaster relief experience induced psychological impacts in the subacute stage. Psychological impacts attenuated one year after the event. In the dispatched group, ALT level significantly increased after the earthquake.